A nondestructive leaf-disk assay for rapid diagnosis of weed resistance to multiple herbicides. Issue 3 (22nd May 2021) - Wu, Chenxi; Varanasi, Vijaya; Perez-Jones, Alejandro
Abstract: Weed resistance surveys that monitor the spread of resistant weeds have mainly been conducted through time-consuming, labor-intensive, and destructive greenhouse herbicide screens. As an alternative, we introduce here a nondestructive leaf-disk assay based on chlorophyll fluorescence ( F v / F m values that measure photosynthetic efficiency) that allows the detection of resistance to both systemic and contact herbicides within ∼48 h. The current study validated the assay for detecting resistance to fomesafen, glyphosate, and dicamba in Palmer amaranth ( Amaranthus palmeri S. Watson), waterhemp [ Amaranthus tuberculatus (Moq.) Sauer], kochia [ Bassia scoparia (L.) A.J. Scott], and goosegrass [ Eleusine indica (L.) Gaertn.]. Negative correlation between F v / F m values and spray injury levels was observed in all herbicide–weed combinations at the discriminating doses, except for glyphosate in Amaranthus . The correlation coefficients were −0.41 for fomesafen (10 µM, P < 0.0001) in Amaranthus, −0.92 for glyphosate in E. indica (250 µM, P < 0.0001), and −0.44 for dicamba in B. scoparia (800 µM, P = 0.0023). At the population level, the assay clearly separated susceptible from highly resistant populations. However, the assay showed lower sensitivity in distinguishing populations of different resistance levels or separating populations with low resistance from susceptible populations. At the individual plant level, results from the leaf-disk assay and whole-plant spray tests were concordant in 85.5%, 92.3%, and 71.7% of the plants tested for fomesafen– Amaranthus, glyphosate– Eleusine, and dicamba– Bassia, respectively. The assay yielded 1% to 15% false-positive and 6% to 13% false-negative results across herbicides. The current study demonstrated that the leaf-disk assay is a useful tool to identify weed resistance. Optimization is needed to improve its sensitivities and expand its usage to more diverse herbicide–weed species combinations.